Anxiety And Short Distance Running Performance In Female Athletes - Kahiji, Ikina Rizki; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Indonesian Journal of Physical Education and Sport Science, 2024)
Studi purpose. There are many cases in athletics where performance declines, especially in women, due to excessive anxiety. Often, they think this is a normal thing, but this can have fatal consequences and interfere with the performance of female athletes in short-distance running events. Thus, this study aims to examine the relationship between anxiety and short-distance running performance in female athletes. Materials and methods. The method used in this research is a descriptive method with a quantitative approach involving 12 female athletes aged 12-15 years. This research uses a total sampling technique. The instrument in this research is the Competitive Sport Anxiety Inventory-2 (CSAI-2) which also takes the results of the 100m sprint data in the Portue 2023 competition to determine the performance of short-distance running athletes. Data analysis was carried out using SPSS version 25 using the Pearson correlation test. Results. The results of the study show that there is a significant relationship between anxiety and the short distance running performance of female athletes. Conclusions. The author can conclude that the anxiety experienced by female track and field athletes, especially in the 100m sprint event, must be managed as well as possible because if not, it can cause female track and field athletes to experience a decline in performance.